1971
DOI: 10.1002/pol.1971.150090909
|View full text |Cite
|
Sign up to set email alerts
|

Chemical thermodynamics of polymerization of formaldehyde in an aqueous environment

Abstract: synopsisA self-consistent set of chemical thermodynamic values for the polymerization of formaldehyde in the gas phase and in aqueous solution is obtained with the aid of recent experimental thermochemical results and the use of selected methods of calculation of data not otherwise available. Enthalpies, entropies, and Gibbs free energies of formation are derived for the various intermediates and products, including the first six hydroxyl-terminated oligomers. Simple equations for the logarithm of the equilibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 16 publications
2
24
0
Order By: Relevance
“…The loss of 16% of the mass at a temperature less than 443 K is associated with the evaporation of water and is accompanied by a significant absorption of heat. An increase in temperature from 443 to 513 K is accompanied by a loss of about 6% of the mass and low heat absorption, which indicates the development of slow depolymerization of formaldehyde oligomers and is consistent with a small value of the formaldehyde polymerization enthalpy (21). In the temperature range from 513 to 603 K, there is a high rate of mass loss, which is presumably associated with the cleavage of the end groups due to homolysis of S-S bonds, which should also lead to the release of sulfur and rapid depolymerization of the remaining formaldehyde oligomers.…”
Section: Resultssupporting
confidence: 68%
“…The loss of 16% of the mass at a temperature less than 443 K is associated with the evaporation of water and is accompanied by a significant absorption of heat. An increase in temperature from 443 to 513 K is accompanied by a loss of about 6% of the mass and low heat absorption, which indicates the development of slow depolymerization of formaldehyde oligomers and is consistent with a small value of the formaldehyde polymerization enthalpy (21). In the temperature range from 513 to 603 K, there is a high rate of mass loss, which is presumably associated with the cleavage of the end groups due to homolysis of S-S bonds, which should also lead to the release of sulfur and rapid depolymerization of the remaining formaldehyde oligomers.…”
Section: Resultssupporting
confidence: 68%
“…Thermodynamic investigation of the polymerization of aldehydes, especially formaldehyde and halogen-substituted aldehydes, has been reported by several workers. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Equilibrium anionic polymerization of P-methoxypropionaldehyde (O=CHCH2CH20CH3, MPA) and n-valeraldehyde (O=CHCH2CHzCH2CH3) has recently been studied in order to estimate the effects of polar substituents on the polymerizability of aliphatic aldehydes, suggesting that the polymerizability is influenced by the intermolecular interactions through polar groups in monomers and their polymer^. '^,^^…”
Section: Introductionmentioning
confidence: 99%
“…Then, unhydrated formaldehyde is the only reducible species and its concentration could be obtained. Finally, Bryant and Thompson (1971) derived an expression for K h from a consistent set of, partly experimental, thermochemical data. The values of K h obtained by the various authors show a considerable spreading; differences of more than a factor 3 are found.…”
Section: Introductionmentioning
confidence: 99%